Love is served : inspired plant-based recipes from Southern California - Dreux Ellis, Seizan; Holtzman, Rachel (Avery, an imprint of Penguin Random House, 2020)
"Bright, clean, and hip recipes to enchant vegans, vegetarians, and omnivores alike, from plant-based haven Café Gratitude"--